Praca nad bohaterem literackim w kl. IV w szkole bułgarskiej = A Paper on the Literary Hero in Form IV of Bulgarian School - Żelewa, Dobrinka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper represents a model of work on the character of a literary hero in form IV of a bulgarian school, adapted to the pupils'abilities of perception.
Keywords: bohater literacki; szkolnictwo - Bułgaria